Peran Pemimpin Dalam Meningkatkan Kinerja Pegawai Pada Inspektorat Kabupaten Mandailing Natal - Al Hamdi, Aprin; Junita, Audia; Siregar, Nina Siti Salmaniah (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2025)
Leadership plays a crucial role in enhancing employee performance, particularly in government environments such as the Mandailing Natal Regency Inspectorate. This study aims to analyze the role of leaders in enhancing employee performance, describe the level of employee performance, and identify factors that act as obstacles to this process. This study employs a descriptive qualitative approach, utilizing data collection techniques that include observation, interviews, and documentation. The informants in this study include the Regional Inspector, the Assistant Inspector, the Head of the General and Personnel Subdivision, and several employees of the Mandailing Natal Regency Inspectorate. The results of the study show that leaders have three leading roles in improving employee performance, namely personal roles, decision-maker roles, and roles as sources of information. Inspectors play an active role in motivating, making strategic and participatory decisions, and filtering and conveying relevant information to employees. In addition, employee performance has generally improved, but there are still obstacles, including low work discipline, a lack of firmness in enforcing rules, and limited human resources and employee training.